Question
upstudy study bank question image url

\( 3 \sqrt[3]{5 y+1}-2=-5 \) The solution set is

Ask by Hammond Gough. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution is \( y = -\frac{2}{5} \).

Solution

We start with the equation:   3∛(5y + 1) - 2 = -5 Step 1: Add 2 to both sides to isolate the cube root term:   3∛(5y + 1) = -5 + 2   3∛(5y + 1) = -3 Step 2: Divide both sides by 3:   ∛(5y + 1) = -1 Step 3: Cube both sides to eliminate the cube root:   5y + 1 = (-1)³   5y + 1 = -1 Step 4: Subtract 1 from both sides:   5y = -2 Step 5: Divide by 5:   y = -2/5 Thus, the solution set is { -2/5 }.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the equation \( 3 \sqrt[3]{5y+1} - 2 = -5 \), let's first isolate the cube root. Adding 2 to both sides gives: \[ 3 \sqrt[3]{5y+1} = -3 \] Now, dividing by 3: \[ \sqrt[3]{5y+1} = -1 \] Next, we'll cube both sides: \[ 5y + 1 = (-1)^3 \] \[ 5y + 1 = -1 \] Subtracting 1 from both sides: \[ 5y = -2 \] Finally, dividing by 5: \[ y = -\frac{2}{5} \] So the solution set is \( \left\{ -\frac{2}{5} \right\} \). In conclusion, finding those hidden solutions often requires peeling back equations layer by layer, much like solving a mystery! Keep practicing and you’ll be a math detective in no time!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy